An Off-Board Multi-Functional Electric Vehicle Charging Station for Smart Homes: Analysis and Experimental Validation - Vitor Monteiro; Pedro Lima; Tiago J. C. Sousa; Julio S. Martins; Joao L. Afonso (Energies, 2020)
This paper presents the analysis and experimental validation of a single-phase off-board multi-functional electric vehicle (EV) charging station (MF-EVCS), which has a single ac interface and two dc interfaces. As innovative aspects, the proposed MF-EVCS handles the interface of the ac power grid, the dc interface of a renewable energy source (RES), as well as the dc interface of an EV to perform dc charging or discharging of the batteries (in off-board grid-to-vehicle (G2V) or vehicle-to-grid (V2G) modes). Considering the power grid, the individual operation modes of the RES and the EV interfaces can be considered. Moreover, a combination of these modes is also possible. Besides, the MF-EVCS has as key innovative aspect the possibility of operating as an active power filter (APF), supporting the operation with reactive power and/or selected current harmonics. This possibility can be associated with any of the previous mentioned modes. These new features are framed in two distinct scenarios: in a smart home, where the ac-side current can be determined as a function of the other electrical appliances; in a smart grid, where the ac-side current can be determined as a requisite of the power grid. The proposed power theory, as well as the current control strategies for both ac-side and dc-side of the MF-EVCS, are presented in the paper for all the possible operation scenarios. A laboratory prototype was developed to validate the proposed MF-EVCS and the experimental results confirm its suitability for smart homes.